Diversity and Usage Custom of Plants of Western Himachal Pradesh, India - Part I - and Rekha Bhadauria1, Ajay K. Gautam1*, Mahendra K. Bhatia2 (Journal of Phytology, 2011)
The present study reports the diversity of plant resources of Bilaspur district of Himachal Pradesh, India for their medicinal, traditional and edible uses. Total 98 plant species belonging to 51 different families were documented for their multifarious uses through collecting information by means of questionnaire surveys, participatory observations and field visits. Of total plant species, 44.89% of tree, 38.77% herb and 16.32% shrub were recorded. About 70.40% plants were used in medicinal practices whereas, 38.77% in traditional and 34.69% in edible purposes. The use of above ground parts like leaves (37.75%), fruits and seeds (20.40% each) and other aerial parts, stem, branch, flowers/inflorescence (12.24-3.06%), was found to be higher as compare underground parts include roots, bulb and rhizome ( 8.16%). About 10 types of diseases related to stomach, mouth, cough, cold, skin, blood, vitality & strength, bones, muscles, and other like memory, swelling etc. were found to be cured by plant based medicines. Use of young twigs was higher (39.47%) in different traditional activitiesÃ‚Â  as compare to other plant parts such as, leaves (23.68%), timber (10.51% each) and fruit, bark, spine, powder, latex/ resin, seed and stem (23.68% collectively). It was observed that urbanization posing a threat to the plant diversity of the area as well traditional knowledge and cultural practices of the rural peoples. Key words: Diversity, Bilaspur district, Himachal Pradesh, Medicinal plants, Traditional plants, Edible plants <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Ajay K. Gautam et al. Diversity and Usage Custom of Plants of Western Himachal Pradesh, India - Part I. J Phytol 3/2 (2011) 24-36.